GPT \(x^2-3x+1+\frac{\sqrt{3}}{3}\sqrt{x^4+x^2+1}=0\)
gpt:
\(3\left(x^2-3x+1\right)+\sqrt{3\left(x^4+x^2+1\right)}=0\)
\(\sqrt[3]{x^3+5x^2}-1=\sqrt{\frac{5x^2-2}{6}}\)
Gpt:
\(\sqrt{-x^2+4x+12}-\sqrt{-x^2+2x+3}=\sqrt{3}-x^2\)\(\sqrt{-4x^4y^2+16x^2y+9}-\sqrt{x^2y^2-2y^2}=2\left(x^2+\frac{1}{x^2}\right)\)\(\sqrt{-x^2+3x+4}+\sqrt{-y^2+2y+2}=\sqrt{-x^2+5x+14}\)\(\sqrt{x^2+8}-\sqrt{x^2+3}=\frac{1}{2}\left(3x-1\right)\)gpt:
\(x-\sqrt{x-8}-3\sqrt{x}+1=0\)
\(x^3+\frac{x^3}{(x-1)^3}+\frac{3x^2}{x-1}-2=0\)
GPT: \(x^2-3x+3=\left(3x-\frac{4}{x}+1\right)\sqrt{x-1}\)
GPT
A,\(\sqrt{X+1}+\sqrt{4-X}+\sqrt{4+3X-X^2=5}\)
B,\(\sqrt{X^2-2X+5}=2-\left(X^2-1\right)^4\)
C,\(\left(X-5\right)^3=5\sqrt[3]{2X-9}-3X+6\)
D,\(\left(2X+1\right)\sqrt{\frac{X+1}{X}}=X+2+\sqrt[3]{2X^2+X^3}\)
MN ƠI GIÚP E MAI E ĐI HOK RỒI
ETICH CHO AI TRẢ LỜ NHANH NHẤT
gpt :
1, \(2\left(2\sqrt{1+x^2}-\sqrt{1-x^2}\right)-\sqrt{1-x^4}=3x^2+1\)
2, \(2\sqrt{1-x}+\sqrt{x+1}+3\sqrt{1-x^2}=3-x\)
GPT : \(\sqrt[3]{x+1}+\sqrt[3]{x+2}=1+\sqrt[3]{x^2+3x+2}\)
chương trình giải trí do obama tài trợ:
gpt:\(\sqrt{3x^2-1}+\sqrt{x^2-x}-x\sqrt{x^2+1}=\frac{1}{2\sqrt{2}}\left(7x^2-x+4\right)\)